GABAB receptor ligands for the treatment of alcohol use disorder: preclinical and clinical evidence - Agabio, Roberta; Colombo, Giancarlo (Frontiers in Neuroscience, 2014)
The present paper summarizes the preclinical and clinical studies conducted to define the “anti-alcohol” pharmacological profile of the prototypic GABAB receptor agonist, baclofen, and its therapeutic potential for treatment of alcohol use disorder (AUD). Numerous studies have reported baclofen-induced suppression of alcohol drinking (including relapse- and binge-like drinking) and alcohol reinforcing, motivational, stimulating, and rewarding properties in rodents and monkeys. The majority of clinical surveys conducted to date—including case reports, retrospective chart reviews, and randomized placebo-controlled studies—suggest the ability of baclofen to suppress alcohol consumption, craving for alcohol, and alcohol withdrawal symptomatology in alcohol-dependent patients. The recent identification of a positive allosteric modulatory binding site, together with the synthesis of in vivo effective ligands, represents a novel, and likely more favorable, option for pharmacological manipulations of the GABAB receptor. Accordingly, data collected to date suggest that positive allosteric modulators of the GABAB receptor reproduce several “anti-alcohol” effects of baclofen and display a higher therapeutic index (with larger separation—in terms of doses—between “anti-alcohol” effects and sedation).